How do consumers perceive food safety risks? – Results from a multi-country survey. (December 2022) - Djekic, Ilija; Nikolic, Aleksandra; Mujcinovic, Alen; Blazic, Marijana; Herljevic, Dora; Goel, Gunjan; Trafiałek, Joanna; Czarniecka-Skubina, Ewa; Guiné, Raquel; Gonçalves, João Carlos; Smole-Mozina, Sonja; Kunčič, Ajda; et al.
Abstract: An online survey was distributed to consumers in nine countries in order to investigate their perceptions related to causers of food safety risks, types of food associated with food-borne illnesses and the role of actors in the food supply chain. A total of 2723 respondents have participated in the survey. Results indicated that food hygiene has been recognized as the most important issue associated with food safety risks. Consumers considered meat and meat products as well as egg and egg-based products, as types of food that pose the highest risks to consumer's health. Food processors and food inspection services play the most significant role in food supply chains. Results further revealed that country of origin has the highest influence on consumer perception, opposed to gender with the least influence. Overall, results obtained in this study confirmed the role of food hygiene as the predominant factor in ensuring food safety in the mind of consumers and that animal-originated food has been perceived as the type of food holding higher health risk opposed to food of plant origin. At the same time, these results challenge the trust in food processors and food inspection services.